By the honourable Roger Wolcott Esq; governour of His Majesty's English colony of Connecticut ... a proclamation for a public thanksgiving : ... Thursday the ninth day of November next ... Given under my hand at the council-chamber in New-Haven, this seventeenth day of October ... 1752 (Printed by Timothy Green, printer to the governour and company of the colony abovesaid, 1752)
October 17, 1752 broadside issued by Governor Roger Wolcott of Connecticut, proclaiming November 9th as a day of thanksgiving for all God's blessings.